Pulse Pressure, Cognition, and White Matter Lesions: A Mediation Analysis - Zang, Jiabin; Shi, Jian; Liang, Jianwen; Zhang, Xiaocong; Wei, Wenbin; Yao, Chun; Zhuang, Xiaodong; Wu, Guifu (Frontiers in Cardiovascular Medicine, 2021)
This study aimed to investigate the effects of pulse pressure (PP) on cognition and the role of white matter lesions (WMLs) in mediating this association. We enrolled 3009 participants from the SPRINT-MIND study. Of those, 755 participants underwent brain magnetic resonance imaging. Cognitive tests were summarized in five cognition domains, including global cognition, executive function, attention, memory, and language. Multiple linear regression models were employed to analyze PP in association with cognition, and mediation analysis was applied to determine the role of WMLs in the association between PP and cognition. We found that PP was negatively linear associated with global cognition (β=-0.048, P=0.008), executive function (β=-0.014, P=0.040), attention (β=-0.013, P=0.035), memory (β=-0.021, P=0.045), and language (β=-0.020, P=0.001), respectively. Furthermore, PP was not significantly associated with brain component volume changes, except for WMLs (β=0.029, P=0.044). Additionally, mediation analysis showed that increased WML volume contributed to 10.8% of global cognition, 9.5% of executive function, 10.6% of memory, and 7.2% of language decline associated with PP. Exposure to higher PP levels was associated with poor cognitive performance, and WMLs partially moderated the influence of PP on cognition.